Do We Need to Hold Aspirin Before Cataract Surgery? A Systematic Review and Meta-Analysis of 65,196 Subjects - Abo Zeid, Mohamed; Elrosasy, Amr; Alkheder, Ahmad; Alkousheh, Hazim; Al Azzawi, Mohammad Al Diab; Mohamed, Shrouk F; Alkhateeb, Ameen; Abu Serhan, Hashem (Seminars in ophthalmology, 2025)
Cataract surgery is a common operation, typically carried out on older adults who have many comorbid medical conditions. Many of these patients may be undergoing aspirin therapy for diverse cardiovascular causes. Nevertheless, there is ongoing controversy regarding the administration of aspirin therapy during the perioperative period, as there are concerns regarding the risk of bleeding problems compared to thromboembolic events. Although aspirin is commonly used, there is no agreement on whether to continue or stop taking it before cataract surgery. This systematic review and meta-analysis attempt to assess the safety of continuing or discontinuing aspirin in the setting of cataract surgery. We conducted a systematic review and meta-analysis following PRISMA guidelines. Four databases were searched until January 25, 2024, for studies assessing the safety and efficacy of aspirin continuation or discontinuation before cataract surgery. The risk ratios (RR) of the extracted data and their 95% confidence interval (95% CI) were pooled using RevMan 5.4 software. We registered our protocol in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42024529986). We included nine studies with a total of 65,196 patients comprising various study designs and global populations. The analysis revealed a significant increase in subconjunctival hemorrhage risk with aspirin continuation (RR: 1.74, 95% CI: 1.22, 2.50, = .002). However, the risk of hyphema, retrobulbar hemorrhage, vitreous hemorrhage, intraocular pressure spike, corneal edema, posterior capsule rupture, and visual acuity changes did not significantly differ between aspirin continuation and discontinuation or aspirin and placebo groups. Although the use of aspirin before cataract surgery raises the likelihood of subconjunctival bleeding, it does not increase the risk of potentially sight-threatening bleeding events. We recommend continuation of aspirin in patients undergoing cataract surgery.